ENGLISH COMMUNICATION ANXIETY AND PEER COMPARISON AMONG INTERNATIONAL CLASS STUDENTS IN BALI - Ningrum, Ida Ayu Fortuna; Cok Istri Agung Sri Wulandari, (Journal of Innovation Research and Knowledge, 2026)
This study investigates English communication anxiety among first-semester students in an international class at a private university in Bali, focusing on peer comparison and support and coping. Drawing on Foreign Language Classroom Anxiety and Social Comparison Theory, it examines how these two factors relate to students’ anxiety. Data were collected from 38 students using a bilingual questionnaire with Likert-scale items and open-ended questions. The results show that students experienced a moderate level of English communication anxiety. Correlation and regression analyses revealed that peer comparison is positively associated with anxiety, whereas support and coping are negatively associated with anxiety. Qualitative responses indicate that students feel both motivated and anxious and that teacher clarity, a relaxed classroom atmosphere, peer encouragement, and gentle correction help them manage anxiety. The findings suggest that EMI programmes need to address affective as well as academic dimensions to build more supportive international-class environments.